The Superstition That Mutilates Children in Africa: Exploring the Scale and Features of Juju-Driven Pedicide in Kenya - Owusu, Emmanuel Sarpong (Homicide studies, 2025)
Juju-involved pedicide is becoming a frequent crime in contemporary African communities. Yet, sparse empirical studies on the subject exist. The present study explores the magnitude, motivations, and primary features of this crime in Kenya. An in-depth analysis was conducted of ritual homicide reports publicized in three Kenyan media outlets between 2012 and 2021. Semi-structured interviews were then conducted with five academics and activists to gain additional insights into key aspects of the results of the content analysis. The data support relevant existing literature that the worst victims of juju-driven murders are children of low socio-economic background in rural communities. The study calls for traditional spiritualists and dubious religious leaders to be brought under closer scrutiny.